Mastering people management : build a successful team : motivate, empower and lead people - Thomas, Mark, 1958- (Thorogood, 2007)
In a time of rapid change and intense competition, the greatest resource for any business is its people. This book explains how to build and develop a successful team by motivating, empowering and leading people. It also provides a practical guide to mastering the essential techniques of people management.